Bentuk makian Bahasa Mandarin di media sosial Wechat - Sunarti, Sunarti; Febrian, Amira Eza Putri (2021)
The phenomenon of using swear word can be said to be a worldwide phenomenon, every country has a language that swears, including China. This type of research used in this research is descriptive qualitative research. This study describes the data in the form of sentences, words and not in the form of numbers, because this research was conducted with a natural setting, namely observation and status data collection written by special WeChat users that contain swear language. The results showed the research data as the form language of invective in social media Wechat consists of three kinds, namely the form of words, phrases and sentence.